Fun Activities to Develop Children's Language and Literacy skills - Harianto II; Nasution, Bincar; Malinda, Risnati; Burhanuddin; Pranawukir, Iswahyu (IJCS: International Journal of Community Service, 2024)
This research study seeks to elucidate the role of educational play in the acquisition of English-language skills among children during their early years. A comprehensive review of pertinent literature was conducted, with a focus on the integration of educational games. The study's primary focus is on early childhood education contexts. This methodology enabled the research team to gain profound insights into the effective integration of educational games in early childhood education. The findings of this study indicate that educational games have a significant positive impact on children's motivation, vocabulary development, and social skills. The researchers have demonstrated that the integration of educational games into the curriculum has resulted in meaningful improvements in the context of daily learning in educational settings. Furthermore, they highlight that these positive effects are not only temporary but also sustained over time. The incorporation of educational games into the curriculum can create a more engaging and interactive learning environment for students, leading to improved quality of learning in the classroom. This study's results lend support to the implementation of dynamic and engaging learning strategies in the early childhood education setting. It is therefore concluded that educational games play an invaluable role in supporting the development of English-speaking skills in this age group.